Developing country fisheries and technical efficiency: the Java Sea purse seine fishery - Jeon, Yongil; Omar, Ishak; Kuperan, K.; Squires, Dale; Susilowati, Indah (2006)
The analysis of technical efficiency in developing country agriculture is well established but has been overlooked for developing country commercial marine fisheries. Policies raising technical efficiency in agriculture are viewed as uniformly positive but are a mixed blessing in fisheries due to the open-access property right and common-pool resource. This study explores this contradiction and policies aimed to promote sustainable development and management of renewable common pool resources through a case study of the Java Sea purse seine fishery. Season of the year rather than fisher or vessel characteristics primarily determines technical efficiency. The results are contrasted with developing country agriculture and conclusions drawn for fisheries development strategies. © 2006 Taylor & Francis